Colostomy irrigation to maintain continence: An old method revived. Issue 8 (August 2016) - Bauer, Carole; Arnold-Long, Mary; Kent, Dea J.
Abstract : Nurses are perfectly positioned to teach appropriate patients how this time-tested method to manage their colostomy can improve their quality of life.